"Looks Can Be Deceiving": Adrenal Teratoma Causing Diagnostic Difficulty. (16th December 2015) - Nadeem, Mehwash; Ather, Muhammad Hammad; Sulaiman, M. Nasir; Pervez, Shahid
Abstract : Teratomas are unusual tumours that derived from totipotent cells with their origin from more than one or usually all three germ cells. Here authors are presenting a case of primary retroperitoneal tumour that is a rare clinical entity. A 19-year-old male presented with right lumbar pain and was found to have complex cyst with large calcification in right adrenal gland on imaging. Intraoperatively, he was found to have a solid mass with areas of soft consistency, which was excised en bloc. On gross examination, the cyst contained pieces of bone, few teeth, and hairs entangled in mucinous material. On histological evaluation, it was confirmed to be mature teratoma arising from the right adrenal gland. He made uneventful recovery and was kept well on annual follow-up.